An Exploratory Study to Identify Barriers to the Implementation of Critical Thinking in Learning English as a Foreign language. Case of Master One LMD Students of English at the University of Souk-Ahras. - Regainia, Meriem (My University, 2023)
Abstract This work attempts to investigate the barriers to implementing critical thinking in English foreign language classes. The purpose of this research is to explore and identify the barriers that hinder the implementation of critical thinking during the learning process. Moreover, this study seeks to raise awareness about the importance of critical thinking in Foreign Language learning. We hypothesize that teachers and students face problems and challenges with the implementation of critical thinking. Another hypothesis is that if the barriers to critical thinking were identified, critical thinking would be more widely implemented by foreign language learners. To prove this hypothesis, a questionnaire has been designed and administered to 55 students chosen randomly from 96 first-year master's students, in addition to a semi-structured interview conducted with teachers to gain more information about their opinions concerning critical thinking and identify the barriers to implementing it in the Foreign Language classroom. Results have shown that students face obstacles and challenges while trying to implement critical thinking during their learning process ---------------- ملخص يحاول هذا العمل استكشاف العوائق التي تحول دون تنفيذ التفكير النقدي في اللغة الإنجليزية فصول لغة أجنبية. الغرض من هذا البحث هو استكشاف وتحديد العوائق التي تعيق تنفيذ التفكير النقدي أثناء عملية التعلم. علاوة على ذلك ، هذه الدراسة يسعى إلى زيادة الوعي بأهمية التفكير النقدي في تعلم اللغات الأجنبية. نفترض أن المعلمين والطلاب يواجهون مشاكل وتحديات في التنفيذ من التفكير النقدي. فرضية أخرى هي أنه إذا تم تحديد العوائق التي تحول دون التفكير النقدي ،سيتم تنفيذ التفكير النقدي على نطاق واسع من قبل متعلمي اللغة الأجنبية. لإثبات ذلك فرضية ، تم تصميم استبيان وإدارته على 55 طالبًا تم اختيارهم عشوائيًا من 96 طالب ماجستير في السنة الأولى ، بالإضافة إلى مقابلة شبه منظمة أجريت معهم أربعة معلمين للحصول على مزيد من المعلومات حول آرائهم فيما يتعلق بالتفكير النقدي و تحديد العوائق التي تحول دون تنفيذها في فصول اللغة الأجنبية. أظهرت النتائج أن الطلاب يواجهون أظهرت النتائج أن الطلاب يواجهون عقبات و تحديات أثناء محاولتهم تنفيذ التفكير النقدي أثناء ذلك ------------------ Résume Ce projet a pour but d’étudier les obstacles de l’utilisation de la pensée critique dans les cours d’anglais comme langues étrangères. Le but de cette étude est de rechercher et d’identifier les obstacles qui nuisent à la mise en pratique de la pensée critique au cours du cycle d’apprentissage. En outre, cette étude vise à mettre en évidence l’importance de la pensée critique dans L’apprentissage de langues étrangères. Nous faisons l’hypothèse que les enseignants et les étudiants sont confrontés à des problèmes et à des difficultés dans l’utilisation de la pensée critique. Une autre hypothèse est que si les obstacles à la pensée critique étaient identifiés, la pensée critique serait plus facilement utilisée par les étudiants de langues étrangères. Pour vérifier cela, un questionnaire a été élaboré et soumis à 55 étudiants choisis au hasard parmi 96 étudiants en première année de master, ainsi que un entretien semi-structuré avec quatre enseignants afin de obtenir plus de informations sur leurs opinions concernant la pensée critique et d’identifier les obstacles à sa pratique dans une classe de langue étrangère. Les résultats ont montré que les étudiants sont confrontés à des obstacles et à des difficultés lorsqu’ils tentent de faire preuve d’esprit critique au cours de leur processus d’apprentissage